Construction of a Biomimetic Magnetosome and Its Application as a SiRNA Carrier for High‐Performance Anticancer Therapy. (7th November 2017) - Zhang, Fan; Zhao, Longjian; Wang, Shumin; Yang, Jun; Lu, Guihong; Luo, Nana; Gao, Xiaoyong; Ma, Guanghui; Xie, Hai‐Yan; Wei, Wei
Abstract: Precisely delivering siRNA to its target site in cancer cells is a high‐demanding but challenging task. Herein, a biomimetic magnetosome is developed using magnetic nanocluster (MNC) as the core and Arg–Gly–Asp (RGD) decorated macrophage membrane as the cloak, which is achieved via a combination of MNC synthesis, azide‐membrane engineering, electrical assembly, and click chemistry. Such a feature‐packed magnetosome enables us to gain the success of high‐performance siRNA delivery through superior stealth effect, magnetic resonance imaging, magnetic accumulation, RGD targeting, and favorable cytoplasm trafficking. As a result, target gene expression can be significantly suppressed and tumor growth is effectively inhibited, while the systemic toxicity is not notable. These results together vote the biomimetic magnetosome as a promising siRNA delivery system for anticancer therapy. Abstract : A biomimetic magnetosome is developed using magnetic nanocluster as the core and Arg–Gly–Asp (RGD) decorated macrophage membrane as the cloak for siRNA delivery to cancer cells. The superior stealth effect, magnetic accumulation, RGD targeting, MR imaging, and favorable cytoplasm trafficking are demonstrated. The target gene expression is significantly suppressed, and significantly inhibited tumor growth is achieved with few side effects.